Pengembangan Profesional Awal Guru Pendidikan Agama Islam dan Strategi untuk Melanjutkan Pengembangannya - Happy Ikmal (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2019)
Teaching is lifelong learning. Turning on all the time, new and old teachers, beginners or professionals will still grapple with how to improve many aspects of teaching, each year demanded to show more improvement. Every idea considers continuing professional development throughout your career. This article examines the following questions: 1. How to start assessing a teacher's professional skills? 2. Do teachers need to understand the standards used by others to assess their professional skills? 3. What model is used to describe the teacher's journey from 'beginner' to 'expert'? 4. How do expert teachers assess themselves and how do they overcome and adapt to change? 5. How can teachers collaborate to make structured observations of their work, as required by the assessment requirements? The results of the discussion concluded: 1) The complexity of assessment that binds teachers and schools continues to increase because assessment is used for various purposes in different contexts; 2) Interstate New Teacher Assessment and Support Consortium (InTASC) was formed to create